Utilization of Medicinal Plants in Kayukebek Village, Tutur District, Pasuruan Regency - Agung Witjoro; Sulisetijono Sulisetijono; Frida Kunti Setiowati (Natural B, Journal of Health and Environmental Sciences, 2016)
Traditional medicine using herbs has been known and done since the first generations by the people of Indonesia. Tutur area is located in the district of Pasuruan, East Java Province. One of the villages in the Tutur area is Kayukebek. The community Kayukebek have knowledge about the advantages of plants as a medicine for specific diseases or health problems. The study aims to: 1) To obtain information the types of plants used as a medicine; 2) To know the various uses of herbs; 3) To determine the perception and appreciation of the herbs from the Kayukebek community. This research is a descriptive explorative study. The method performed in the exploratory survey data collection by direct observation in the field and Participatory Rural Appraisal methods. Community engagement obtained through interviews with semi-structural and open-ended based question list. Sampling technique used is purposive sampling and snowball sampling. The value of the use of plants known by the value of Informant Concencus Factor and Use Value. The results, recorded 22 plants species have been used in this community as traditional medicine, include: garlic, tropong onion (scallion), plantain, dlingo, ceplukan, jambu wer, senggani, blencong, tamarind, kecubung, mustard greens, cabbage, fennel, turmeric, ginger, pulosari, sendokan, corn, white wood, sempretan (brojo lintang), gorogo, and wono ginger. It was observed that the local people are less aware of the medicinal plants. It is seen the public perception of the use medicinal plants is low (48.03%) meanwhile the appreciation medicinal plants are prefer to low category (49.69%).